2006
DOI: 10.1002/job.379
|View full text |Cite
|
Sign up to set email alerts
|

The impact of impression‐management tactics on supervisor ratings of organizational citizenship behavior

Abstract: SummaryPrevious research indicates that the use of impression management is related to supervisor ratings of employee likeability and job performance. It has been argued, though, that employees might also use impression management so that their superiors will see them as 'good soldiers' who engage in high levels of organizational citizenship behaviors (OCBs). This study investigates the ways in which three types of impression management-namely, job-focused, self-focused, and supervisor-focused tactics of impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
217
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(233 citation statements)
references
References 36 publications
7
217
1
3
Order By: Relevance
“…Conceptually, this study is grounded in impression management, since job-related impression management is geared towards appearing more competent (Bolino et al, 2006). The study has revealed that instances of all assertive tactics and strategies introduced are used to create very comprehensive impressions of CEO competence.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, this study is grounded in impression management, since job-related impression management is geared towards appearing more competent (Bolino et al, 2006). The study has revealed that instances of all assertive tactics and strategies introduced are used to create very comprehensive impressions of CEO competence.…”
Section: Discussionmentioning
confidence: 99%
“…Organ (1988) described those who perform OCB as "good soldiers", which implies that the motive behind OCB is purely altruistic [28]. Bolino (1999), Hui et al (2000) and Bolino et al (2006) found that egoistic concerns can also motivate individuals to perform OCB [31,34,35]. Consistent with the framework of altruistic and egoistic concerns, Rioux & Penner (2001) identified three types of motives for OCB: (i) prosocial value, (ii) organizational concern and (iii) impression management [32].…”
Section: Motives Of Employee Voicementioning
confidence: 99%
“…For example, employees could offer some practical suggestions to resolve the interpersonal conflicts among colleagues. When supervisors believe that the voice behavior of the subordinates is driven by an altruistic rather than egoistic motive, they tend to regard the subordinates as "good citizens", which results in positive performance appraisal [35,39,40].…”
Section: Attribution Of the Motives And Performance Appraisal Of Emplmentioning
confidence: 99%
“…Third, the employees need a suitable allocation of obligations especially first line employee to manage the customer with an especial request that needs employees' abilities for optional judgment, which are also related to employees' value system. Many studies mentioned that employees' attitudes and belief shape their behaviors in the system (Organ & Ryan, 1995;Bolino et al 2006). Another group of researchers found that people's differences that come from especial root issues like personal values and traits can predict their abilities in different situations (Cantor & Mischel, 1979;Organ & Konovsky 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the past studies have mentioned the multiple behavior approaches and oriented issues of ability (Moorman, 1991;Penner et al, 1997;Rioux & Penner, 2001;Meglino & Korsgaard, 2004;Bolino et al, 2006). They also mentioned different roots for any reaction and it can recognize that more than one motivational value play essential role in a single action but many of the researcher prefer to check just one or two types of values in their studies (Schwartz & Bilsky, 1990;Kamakura & Novak, 1992;Schwartz, 2011;Saris et al, 2013;Gollan & Witte, 2014).…”
Section: Introductionmentioning
confidence: 99%